Diskursus Penolakan COD (Cash on Delivery ) oleh Konsumen di Media Online dalam Perspektif Hukum Perdagangan - Dewi Rahmawati Gustini (Neolectura, 2022)
The growth of the internet has not only impacted the e-commerce ecosystem, but it has also given rise to a new payment model in buying and selling transactions. Consumers can now get the product first through a courier and then through the courier the payment for the product is made. Various news reports in the mass media show that this COD or Cash On Delivery system from the consumer aspect raises problems in the form of refusal to pay or settle bills. This research uses phenomenological analysis and concludes from online media coverage on Kompas.com, Republika.co.id, and Detik.com that the biggest refusal of consumers is the lack of knowledge of consumers themselves about COD transactions.